PENGARUH LARUTAN JERUK NIPIS DAN GULA PADA DOSIS YANG BERBEDA SEBAGAI LARUTAN PENYEMPROT TERHADAP MORTALITAS, LAMA TETAS, DAN SALEABLE DOD ITIK TEGAL - Lusiana Ayu Pradini; Dian Septinova; Khaira Nova (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The aim of this research was to (1) identify the effect of spray solution (lime and sugar) at different doses on mortality embryo, hatching time and saleable tegal ducks, (2) investigate the best spray solution at different dose on mortality embryo, hatching time and saleable tegal ducks. The research was conducted from 11th December 2015-9th January 2016 at Beruang St, 12 Kedaton, Bandar Lampung. Research using a completely randomized design (CRD) with 2x2 of nested model. The main block is the kind solution (lime and sugar) and the partial block is dosage solution (5% and 10%) with 5 replication. Every unit experimental consist of 3 eggs with average initial weight at 72 ± 1.8 g/egg with coefficient variation ± 2.45%. variables measured were mortality of last three days of hatching, hatching time and saleable DOD tegal ducks. Research data were analyzed by using the assumption of variance on the real level of 5%. The results shows that (1) spray solution (lime and sugar) at different dose give no significant effect (P> 0,05) on mortality, hatching time, and saleable DOD tegal ducks, (2) yet there is the best spray solution at different doses on mortality, hatching time and saleable DOD tegal ducks. Key words: Hatching Time, Mortality, Saleable DOD Tegal Ducks, Solution Dose, Solution of Time, Solution of Sugar